Street-Level Organizations and the "Real World" of Workfare: Lessons from the US - Evelyn Z. Brodkin (Social Work and Society)
By the end of the 20th C., workfare and labor market activation policies had become increasingly common around the globe. These developments provoked debate over whether these policies were advancing a project of commodification (Esping-Andersen 1990) by marketizing citizenship or a project of inclusion by bringing marginalized groups into the economy and society or whether they were advancing inclusion by supporting labor market participation. Assessment of this developments is complicated, in part, by the bewildering array of policy labels under which they have occurred, among them welfare-to-work, labor market activation, jobseekers' allowance, Hartz reforms, and revenu minimum d'insertion. Yet, the many variants of workfare and activation tend to draw on a common assortment of features, among them, potentially enabling provisions for training and work. The shift toward conditionality in benefits is part of a broad trend that, in some countries, has eroded or even replaced rights-based benefits that were previously conditioned primarily on need, legal right (e.g., compensation to unemployed workers), or family status (e.g, welfare benefits for families with children).